Exploring the role of the key gene TNFAIP3 between periodontitis and influenza A through bioinformatic analysis and molecular docking - Mingxiang Xu; Jiaxin Shi; Yang Wang; Jie Wu; Qiaozhi Yang; Weiyun Chen; Yinpeng Li; Luwei Zhang; Xin Liu; Fu Ren; Yudong Wu; Lin Ye; et al. (PLoS ONE, 2026)
Recent studies have hinted at a link between periodontitis (PD) and influenza A (IA). Therefore, this study aims to identify key genes common to both diseases by studying Porphyromonas gingivalis ( P.gingivalis ) and the H1N1 virus, the main pathogen of PD and IA, evaluating the promise of these genes as biomarkers, and providing future therapeutic strategies for both diseases. Our research employs a wide range of methods, including bioinformatics analysis, drug prediction and molecular docking. Ultimately, machine learning algorithms identified TNFAIP3 as a common key gene for PD and IA, and further identified five drugs: Vemurafenib, Metformin, Dexamethasone, Tretinoin and Imatinib with potential for combined treatment of PD and IA. Our study reveals the shared mechanism and immune profile of TNFAIP3 as a key gene in PD and IA, which lays a theoretical foundation for future targeted therapies based on the shared mechanism of the two diseases.